Sosialisasi Mengenai Pentingnya Jaminan Kesehatan - Gusti Agung Sri Guntari (Lembaga Pengembangan Kinerja Dosen, 2023)
Health insurance is one of the essential needs for all people, as an effort to protect themselves from financial burdens when experiencing health problems. The health insurance in question can be a social health insurance organized by the government, which is currently known as the National Health Insurance (JKN) or private health insurance. This socialization was held as a forum to increase participants' knowledge and awareness about the importance of having health insurance as an effort to protect finances when experiencing health problems. Socialization is carried out online to informal workers in the Gianyar Regency environment. With this socialization, it is hoped that Universal Health Coverage for all Indonesian people can be achieved, and there will be no more people who are unable to access health services due to cost constraints.